Impact of Climate Change on Water Resources in the Wadi Guir Watershed: Adaptation Strategies for Sustainable Management - Messaoudi Badre; Kabiri Lahcen; Ait Lahssaine Ismail; El Hafyani Mohammed; Kadiri Abdelhakim; Essafraoui Badre; Albergel Jean (E3S Web of Conferences)
The Wadi Guir Watershed, located in the eastern basins of Morocco, spans approximately 4,231 km². One of the major challenges both globally and in Morocco, particularly in oasis regions such as the Guir River watershed, is ensuring water availability while preserving ecosystems in arid zones affected by climate change. This challenge is further compounded by the development of modern intensive agriculture alongside traditional oasis systems.This study aims to evaluate the impact of climate change on water resources in the Wadi Guir watershed, focusing on the most critical scenario, RCP 8.5, for the period from 2019 to 2060. A statistical downscaling model and the non-parametric Pettitt test were employed to analyze precipitation trends in the region. The results reveal a decline in precipitation under the selected scenario, coupled with an increase in temperatures. Consequently, a reduction in discharge is projected, from 0.045 Mm³ in 2019 to 0.030 Mm³ in 2060, alongside intensified evaporation.This research highlights the urgent need to develop adaptation strategies and decision-making frameworks tailored to the impacts of climate change to ensure the sustainable management of natural resources and ecosystems.